2021
DOI: 10.47115/jshs.969748
|View full text |Cite
|
Sign up to set email alerts
|

Covi̇d-19 Salgininda Ebeli̇k Öğrenci̇leri̇ni̇n Si̇berkondri̇ Düzeyleri̇ Ve Etki̇leyen Faktörleri̇n İncelenmesi̇

Abstract: Amaç: Bu çalışma, Covid-19 salgınında ebelik öğrencilerinin siberkondri düzeyleri ile etkileyen faktörlerin belirlenmesi amacıyla yürütülmüştür.Yöntem: Tanımlayıcı desende yürütülen çalışmanın örneklemini, bir kamu üniversitesinin Sağlık Bilimleri Fakültesi Ebelik Bölümü'nde öğrenim gören 308 öğrenci oluşturdu (Katılma Oranı: %93). Çalışmaya katılmayı kabul eden öğrencilere, "Kişisel Bilgi formu" ve "Siberkondri Ciddiyet Ölçeği (SCÖ)" uygulandı. Bulgular: Araştırmaya katılan öğrencilerin yaş ortalamasının 20.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…According to the data, the mean total score of the students’ ETS was 67.75. In the studies conducted by Aydın and Aker (2020) and Oran and Kurul (2019), the empathic tendencies of midwifery students in Turkey were also found to be at a moderate level [ 21 , 22 ]. Our study results are similar to other studies with midwifery students in different populations around the world [ 9 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the data, the mean total score of the students’ ETS was 67.75. In the studies conducted by Aydın and Aker (2020) and Oran and Kurul (2019), the empathic tendencies of midwifery students in Turkey were also found to be at a moderate level [ 21 , 22 ]. Our study results are similar to other studies with midwifery students in different populations around the world [ 9 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the study conducted by Aydın and Aker (2020) with midwifery students, it was found that the empathic tendency of students who willingly chose the profession was higher. In another study, the empathic tendencies of midwives who willingly chose the profession were determined to be higher [ 21 , 26 ]. Knowing and willingly choosing the profession is very crucial in terms of both enhancing the motivation of students and achieving professional satisfaction, which also positively affects students’ empathic tendencies.…”
Section: Discussionmentioning
confidence: 99%